Early marriage, bride price and the practice of dowry in Bangladesh villages - Hadi, Abdullahel (BRAC Research and Evaluation Division (RED), 2019)
This study estimates the incidence and correlates of early marriage and the practice of dowry in rural Bangladesh. Data for this research came from Watch, a surveillance system of BRAC covering 70 villages in I 0 regions of the country. The incidence of early marriage was reported 60.~% and the dowry practice was 50.1% in 1996. Findings reveal that such socioeconomic factors as the education of spouses, amount of land owned, socioeconomic status and media exposure has reduced the incidence of early marriage and practice of dowry while increased the amount of bride prices. Hindus were more likely to practice dowry than Muslims. The participation in micro-credit programme has not played any significant role in reducing early marriage and dowry practices in rural Bangladesh.